(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
I propose a reading of Di Giorgio’s erotic stories according to which generic textual and sexual hybridism widely recognized by critics, as well as the recurrence of transformations and metamorphosis at the urging of a desire that cancels the boundaries between the human, animal, vegetable and material, he makes a deep epistemological critique of modern rationality, andro and anthropocentric, and his way of conceiving identity and difference. The axis of this epistemological rupture is the disarticulation of the sex/gender and nature/culture binary structures, which dislocate the alignment of body-gender-desire and the classic bios/zoé opposition, fundamental bases of the political and symbolic orders of the West.